1986
DOI: 10.1128/mcb.6.10.3550
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional enhancer and an interferon-responsive sequence in major histocompatibility complex class I genes.

Abstract: The major histocompatibility complex class I antigens play an indispensable role in cell-cell interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…This similar sequence was in the opposite orientation, consistent with the enhancerlike capacity of the ISG15 5'-flanking sequence (Reich et al 1987). Other genes known to be strongly induced by IFN, such as 6-16 (Porter et al 1988), C202 ISamanta et al 1986, and H-2 Vogel et al 1986), also contain a strong homology limited to about 15 nucleotides. This region of homology is much smaller, but it is contained within the sequence predicted previously by Friedman and Stark (1985) on the basis of sequence comparison alone for genes whose sequences were known (metallothionine and histocompatibility genes) but whose IFN-responsive regions had not been identified.…”
Section: Genes and Development 385mentioning
confidence: 61%
“…This similar sequence was in the opposite orientation, consistent with the enhancerlike capacity of the ISG15 5'-flanking sequence (Reich et al 1987). Other genes known to be strongly induced by IFN, such as 6-16 (Porter et al 1988), C202 ISamanta et al 1986, and H-2 Vogel et al 1986), also contain a strong homology limited to about 15 nucleotides. This region of homology is much smaller, but it is contained within the sequence predicted previously by Friedman and Stark (1985) on the basis of sequence comparison alone for genes whose sequences were known (metallothionine and histocompatibility genes) but whose IFN-responsive regions had not been identified.…”
Section: Genes and Development 385mentioning
confidence: 61%
“…Recently, Vogel et al (43) have shown that the transient expression of a CAT gene directed by 1.9 kb of the 5' flanking region of the H-2Ld gene is not down-regulated in adenovirus type 12-transformed cells, even though the level of transcription of endogenous h-2 genes in these cells is only 5% of the normal cell level. It is possible that the data from this system are analogous to our own data relating to the M-MSV effect on transient expression of a CAT gene directed by 2.1 kb of H-2Kb 5' flanking region.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The binding sites on DNA for ISGF3, called IFN-stimulated response elements (ISREs), are found near promoters of most IFN-␣/␤-responsive genes (7,19,31,33,34,48). The ISGF3 transcription factor is an oligomeric protein with three subunits: STAT1, STAT2, and a 48-kDa DNA-binding protein (9,10,38,46).…”
mentioning
confidence: 99%